Rumah Dato' Gempa Maharaja Haji Mohd Zakaria, Chengkau, Rembau Negeri Sembilan / [lukisan teknik] - Idham Baharuddin; Mohd. Rizalludin Ahmad; Tengku Ahmad Ismawi Tengku Ismail; Wan Mohammad Wan Mahmood; Muhammad Faiz Ramli; Erda Rosniza Roslan (Skudai : Universiti Teknologi Malaysia, 1997)
Kajian Lukisan Terukur (Jabatan Senibina ) - Univesiti Teknologi Malaysia, 1997